iPSC models of mitochondrial diseases - Sonja Heiduschka; Alessandro Prigione (Neurobiology of Disease)
Mitochondrial diseases are historically difficult to study. They cause multi-systemic defects with prevalent impairment of hard-to-access tissues such as the brain and the heart. Furthermore, they suffer from a paucity of conventional model systems, especially because of the challenges associated with mitochondrial DNA (mtDNA) engineering. Consequently, most mitochondrial diseases are currently untreatable. Human induced pluripotent stem cells (iPSCs) represent a promising approach for developing human model systems and assessing therapeutic avenues in a patient- and tissue-specific context. iPSCs are being increasingly used to investigate mitochondrial diseases, either for dissecting mutation-specific defects within two-dimensional (2D) or three-dimensional (3D) progenies or for unveiling the impact of potential treatment options. Here, we review how iPSC-derived 2D cells and 3D organoid models have been applied to the study of mitochondrial diseases caused by either nuclear or mtDNA defects. We anticipate that the field of iPSC-driven modeling of mitochondrial diseases will continue to grow, likely leading to the development of innovative platforms for treatment discovery and toxicity that could benefit the patient community suffering from these debilitating disorders with highly unmet medical needs.